2022
DOI: 10.1093/plcell/koac056
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast translational regulation uncovers nonessential photosynthesis genes as key players in plant cold acclimation

Abstract: Plants evolved efficient multifaceted acclimation strategies to cope with low temperatures. Chloroplasts respond to temperature stimuli and participate in temperature sensing and acclimation. However, very little is known about the involvement of chloroplast genes and their expression in plant chilling tolerance. Here we systematically investigated cold acclimation in tobacco seedlings over two days of exposure to low temperatures by examining responses in chloroplast genome copy number, transcript accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 104 publications
3
34
0
Order By: Relevance
“…Cold stress signaling above freezing temperature triggered various physiological processes to ameliorate the deleterious effects on plant cellular organs, referred to as cold or chilling acclimation. Among the immediate physiological response, cold stress reduced the chlorophyll fluorescence trait (maximum quantum efficiency of PSII) (Fv/Fm) in the dark-adapted state and impaired the photosynthesis process (Gao et al, 2022). Similarly, we observed a significant reduction in Fv/Fm under cold stress conditions from 0.105 to 0.790 compared to control conditions from 0.719 to 0.883 (Figure 1B).…”
Section: Evaluation Of Chlorophyll Fluorescence Parameter Fv/fm In So...supporting
confidence: 63%
See 3 more Smart Citations
“…Cold stress signaling above freezing temperature triggered various physiological processes to ameliorate the deleterious effects on plant cellular organs, referred to as cold or chilling acclimation. Among the immediate physiological response, cold stress reduced the chlorophyll fluorescence trait (maximum quantum efficiency of PSII) (Fv/Fm) in the dark-adapted state and impaired the photosynthesis process (Gao et al, 2022). Similarly, we observed a significant reduction in Fv/Fm under cold stress conditions from 0.105 to 0.790 compared to control conditions from 0.719 to 0.883 (Figure 1B).…”
Section: Evaluation Of Chlorophyll Fluorescence Parameter Fv/fm In So...supporting
confidence: 63%
“…Similarly, cold or freezing tolerant poplar maintained higher qL and Fv/Fm by protecting the photosystem (He et al, 2019). In previous studies, comparative RNA-seq analysis showed upregulation of several photosynthetic genes in response to cold in tobacco and M. × giganteus (Spence et al, 2014;Gao et al, 2022). The chloroplast is the primary biosynthesis place of defense-related hormones (Bwalya et al, 2022); therefore, we determined whether photosynthesis genes are involved in cold defense in soybean.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Chloroplast protein synthesis undergoes fast and global reorganization during heat acclimation in the green alga Chlamydomonas and the seed plant tobacco ( Trösch et al., 2022 ). Recently, translational regulation of chloroplasts was shown to play an important role in plant responses to chilling stress ( Gao et al., 2022 ). Mutations in chloroplast translation initiation factor FUG1 ( IF2 ) and ribosomal proteins reduce chilling tolerance in Arabidopsis and tobacco ( Rogalski et al., 2008 ; Marino et al., 2019 ).…”
Section: Translational Control Of Chloroplast-encoded Proteinsmentioning
confidence: 99%